One-Step PCR Detection of Salmonella Pullorum/Gallinarum Using a Novel Target: The Flagellar Biosynthesis Gene flhB - Xiong, Dan; Song, Li; Geng, Shizhong; Tao, Jing; An, Shumin; Pan, Zhiming; Jiao, Xinan (Frontiers in Microbiology, 2016)
Salmonella enterica serovar Pullorum/Gallinarum is an important infectious pathogen that has caused widespread problems for chicken industry. Traditional Salmonella serotyping is an expensive and time-consuming process. In this study, we developed a rapid one-step PCR method to identify S. Pullorum/Gallinarum. The PCR-based assay focuses on flhB, which shows a deficient region only in S. Pullorum/Gallinarum, compared with that of other serovars. The specificity and sensitivity of the PCR system were evaluated. The developed PCR method could identify S. Pullorum/Gallinarum from 27 different Salmonella serovars and eight non-Salmonella pathogens. The minimum limit of DNA and the lowest number of cells of S. Pullorum for the PCR detection were no less than 5.85 pg/μL and 10 CFU, respectively. The method was applied to the analysis of Salmonella strains isolated from the chicken farm. The PCR-based testing results of the farm isolates were in concordance with those obtained using traditional serotyping method. This newly developed PCR-based system could be used to accurately screen for the presence of S. Pullorum/Gallinarum, and support traditional serotyping methods, especially in high-throughput screening situations.